The Effects of Early Tracking on Student Performance: Evidence from a School Reform in Bavaria - Marc Piopiunik (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
This paper evaluates a school reform in Bavaria that moved the timing of tracking in low- and middle-track schools from grade 6 to grade 4; students in high-track schools were not affected. To eliminate state specific and school-type-specific shocks, I estimate a triple-differences model using three PISA waves. The results indicate that the reform reduced the performance of 15-year-old students both in low- and middle-track schools. Further evidence suggests that the share of very low-performing students increased in low-track schools.
Keywords: I20; I21; I24; 330; Tracking; student performance; PISA